Assessing the adherence to guidelines in the management of croup in Australian children: a population-based sample survey. (28th October 2019) - Prentice, Bernadette; Moloney, Susan; Hort, Jason; Hibbert, Peter; Wiles, Louise K; Molloy, Charlotte J; Arnolda, Gaston; Ting, Hsuen P; Braithwaite, Jeffrey; Jaffe, Adam
Abstract: Objective: To determine the extent to which care received by Australian children presenting with croup is in agreement with Clinical Practice Guidelines (CPGs). Design: Retrospective population-based sample survey. Croup clinical indicators were derived from CPGs. Data sources/study setting: Medical records from three healthcare settings were sampled for selected visits in 2012 and 2013 in three Australian states. Data collection: Data were collected by nine experienced paediatric nurses, trained to assess eligibility for indicator assessment and adherence to CPGs. Surveyors undertook criterion-based medical record reviews using an electronic data collection tool. Results: Documented guideline adherence was lower for general practitioners (65.9%; 95% CI: 60.8–70.6) than emergency departments (91.1%; 95% CI: 89.5–92.5) and inpatient admissions (91.3%; 95% CI: 88.1–93.9). Overall adherence was very low for a bundle of 10 indicators related to assessment (4.5%; 95% CI: 2.4–7.6) but higher for a bundle of four indicators relating to the avoidance of inappropriate therapy (83.1%; 95% CI: 59.5–96.0). Conclusions: Most visits for croup were characterized by appropriate treatment in all healthcare settings. However, most children had limited documented clinical assessments, and some had unnecessary tests or inappropriate therapy, which has potential quality and cost implications. Universal CPG and clinical assessment tools may increase clinical consistency.